Effect of abiotic factors on pathotypes causing yellow and brown rust in wheat - SHUBHAM ANAND; SARABJOT KAUR SANDHU; PARMINDER SINGH TAK (Journal of Agrometeorology, 2023)
An attempt was made to determine the most favourable abiotic factors influencing germination of urediniospores of different pathotypes of Puccinia species. The causal organism of rusts in wheat is Puccinia spp. Five pathotypes of Puccinia striiformis (46S119, 78S84, 110S84, 110S119, 238S119) causal organism of yellow rust and two pathotypes of Puccinia triticina (77-5 and 77-9) causal organism of brown rust in wheat were obtained from Department of Plant Pathology, Punjab Agricultural University, Ludhiana. The data related to spore germination on agar slides was analysed and the levels of urediniospores germination at different temperatures (5,10,15 and 20oC) and pH (5,6,7 and 8) for each pathotype was compared using analysis of variance. The most appropriate temperature and pH were later used to conduct an experiment to study effect of different light intensities (500, 750,1000 and 1250 lux) on spore germination of all the pathotypes under study. The data showed that on agar, 15°C was proved as most suitable for urediniospore germination for Puccinia striiformis. Mean per cent spore germination was highest over the temperature range 15°C (43.55%) for Pst pathoypes and dropped significantly at 10°C (37.97%), 20°C (29.66%) and 5°C (21.04%). Mean urediniospore germination for Puccinia triticina was highest at 20°C (43.89%) followed by 15°C (39.44%), 10°C (30.43) and 5°C (27.39% ). Experimental results revealed that per cent spore germination was better under pH 7 followed by 6, 5 and 8 for all the pathotypes considered for study. The highest urediniospore germination was observed for 1250 lux (46.54%) followed by 1000 lux (41.29%), 750 lux (38.42%) and 500 lux (27.60%).